The Shoshoolog: Ethnonym and Ethnic History - Bair Z. Nanzatov; Vladimir V. Tishin (Монголоведение (Монгол судлал), 2021)
Introduction. This article under takes a study of the clan name Shoshoolog (Šošōlog) in the context of ethnogenesis and ethnic history of the Mongolic and Turkic peoples of Inner Asia and Siberia. New historical and ethnographical data, including the evidence of ethnonymics as a part of the ethnic history of the Mongolic and Turkic peoples of the region will contribute to the knowledge of the migration and settlement history of the Shoshoolog people. The study aims at examining the etymology of the term šošōloγ, the area where it wasspread and theways of itsspread. Data and methods. The authors have taken into account written documents, ethnographical and folklore sources that contained references to the ethnonym in question. The written sources of the period between the seventeenth and nineteenth centuries, mainly in Russian, such as Cossacks’ otpiski (reports), and, more recent, travel and census reports, contain various forms of the ethnonym, often incorrectly spelled but still of interest as evidence pointing at the settlement areas of the ethnic group, as well as a source for linguistic speculation. The ethnographical sources include references to the ethnic group in question based on the legends and sagas shedding light on the people’s origin and settlement patterns both in the Baikal area and in Mongolia. The folklore texts written down by N. N. Poppe, S. P. Baldaev, etc. Include the stories of the Shoshoolog as a Buryat clan with a strong Shamanic background, as well as various forms of the ethnonym. Granted the available knowledge of the historical patterns in the language evolution, the orthographical forms of the ethnonym contained in different records were used as the data for further phonetical reconstructions and localizations of the ethnonym’s phonetic shape in terms of chronological and geographical dimensions. This data, alongside other material on the ethnonymics and onomastics of Mongolic and Turkic peoples, contributes to the linguistic part of the database in the field. Conclusions. A ...